2008
DOI: 10.1088/1126-6708/2008/10/020
|View full text |Cite
|
Sign up to set email alerts
|

Sakai-Sugimoto brane system at high density

Abstract: The D4-D8 brane system of Sakai-Sugimoto model at high quark density is studied in the weak coupling regime. We show that the color superconducting phase (for N c ≈ 3) or the chiral density wave (for N c → ∞) disappears at very large chemical potential, or equivalently at very large compactified dimension that the model possesses. We also comment on the prospects in the strong coupling regime along with the QCD phase diagram.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…That model also displays a first-order meson melting transition as described in [195,211]. Additional finite density studies can be found in [173,174,[212][213][214][215][216][217]. As an example we consider here spectral functions at finite temperature and the quark chemical potential as discussed in [209].…”
Section: More Thermodynamicsmentioning
confidence: 98%
“…That model also displays a first-order meson melting transition as described in [195,211]. Additional finite density studies can be found in [173,174,[212][213][214][215][216][217]. As an example we consider here spectral functions at finite temperature and the quark chemical potential as discussed in [209].…”
Section: More Thermodynamicsmentioning
confidence: 98%
“…16 The scalar mesons feel the chemical potential through the commutators in the covariant derivatives. The equation of motion for the scalars in the I and σ 3 directions are unaffected by the chemical potential (4.2), while the equations for the σ 1 and σ 2 components are easily generalized from those in [10].…”
Section: Transverse Vectors and Scalarsmentioning
confidence: 99%
“…In the holographic QCD model, a chemical potential for baryon number corresponds to a nonzero asymptotic value of the electrostatic potential on the D8-branes [25,26,27,28,29,30,31]. In our model, a constant baryon chemical potential has been naively introduced.…”
Section: Conclusion and Discussionmentioning
confidence: 99%